‘Dare to Shine’: Megan Rapinoe as the Rebellious Star of the FIFA Women's World Cup 2019 - Turtiainen Riikka (Emerald, 2025)
In 2019, FIFA Women's World Cup turned into a mega event with enormous viewing figures. The U.S. player Megan Rapinoe became a star of the tournament on and off the field. Her controversial presence as an outspoken athlete-activist gained attention worldwide. In this chapter I examine her representations in social and mainstream media during the World Cup. In context of social media I focus on her Instagram posts and ephemeral stories with ethnographic observation and field notes. I utilize feminist thematic analysis of female athletes’ self-representation strategies on social media. The key concepts emphasizing neoliberal post-feminism here are self-love, self-disclosure and self-empowerment. (Toffoletti & Thorpe 2018.) As a result, I argue that the time is finally right for the new kind of recognition of women’s football and therefore need for a rebellious female athlete who takes advantage of this opportunity to raise awareness of equality among (sports) people.
Sport, Gender and Mega-Events